PENGARUH JOB INSECURITY, KEPUASAN KERJA, DAN KOMITMEN ORGANISASIONAL TERHADAP KEINGINAN BERPINDAH KERJA - Utami, Intiyas; Bonussyeani, Nur Endah Sumiwi (Jurnal Akuntansi dan Keuangan Indonesia, 2009)
Lecturers are expected to perform Tri Dharma Perguruan Tinggi involving education and learning, research, and devotion to society. In executing the job, lecturers might feel uncomfortable, nervous, insecure, wony, and powerless toward the continuity his job (job insecurity). The higher the job insecurity, the lower the job satisfaction and organizational commitment, resulting in higher turnover intention. The purpose o f this study is to investigate the direct influence o f job insecurity on turnover intentions and the indirect influence o f job insecurity on the relationships between job satisfaction, organizational commitment and turnover intentions. The sample is taken from accounting lectures at Christian Universities o f Central Java and Special District o f Jogjakarta. We use survey method with convenience sampling approach. This study uses simple regression method and multiple regressions to test the hypotheses developed in this study. The results o f the study show that job insecurity positively and significantly influences turnover intentions. The results also show that job insecurity negatively and significantly influences turnover intention through job satisfaction and organizational commitment.